Into the Emancipated Curriculum: Teachers’ Perceptions of the Curriculum Change - Kusumawati, Maulidiya; Istiadi, Nabila Yumna; Fristiana, Shinta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The transition from the 2013 Curriculum to the Emancipated Curriculum represents a pivotal change in Indonesian education aimed at improving educational quality and relevance. This study explores teachers’ perceptions of this curriculum change, focusing on its implementation challenges and benefits. Employing a qualitative descriptive research design, the study utilizes narrative inquiry through semi-structured interviews with teachers directly involved in the transition process. Key findings reveal challenges such as reduced teaching time and curriculum constraints, alongside benefits including increased creativity and enhanced integration of technology. Teachers’ perceptions underscore the critical role of adaptability in navigating curriculum change effectively. The study highlights implications for enhancing educational practices and student outcomes in Indonesia, emphasizing the need for supportive policies and professional development to facilitate successful curriculum implementation. By understanding teachers’ experiences and insights, this research contributes to refining educational strategies that align with current needs and aspirations, promoting a more responsive and effective educational system. Keywords: Curriculum Change, Educational Reform, Emancipated Curriculum, Indonesia, Teacher Perceptions